Synchrotron radiation of a single electron application for optical spectroradiometry - A. S. Sigov; E. R. Lazarenko; N. B. Golovanova; O. A. Minaeva; S. I. Anevsky; R. V. Minaev; P. Yu. Pushkin (Российский технологический журнал)
Objectives. The investigations of optical radiation sources and metrological detector characteristics in the infrared (IR), visible, and air ultraviolet (UV) spectral regions are partially based on the unique metrological properties of synchrotron radiation. The aim of this work is to develop a high-precision method for determining the storage ring accelerated electron number with synchrotron radiation of a single electron to establish spectroradiometry and photometry units.Methods. By determining the number of accelerated electrons, any storage ring can be used to calculate the synchrotron radiation characteristics at wavelengths of many large then the critical wavelength in the visible, air UV, and IR regions of the spectrum. This makes it possible to determine the main metrological characteristics normalized to the number of electrons, such as luminous intensity, luminance, illuminance, radiant power, radiance, irradiance, etc., regardless of the energy of the electrons.Results. When applying the method for determining the number of accelerated electrons at low currents of the electronic storage ring, a total standard deviation of the number of accelerated electrons is less than 0.01% for an exposure range of the CCD matrix from 10−2 to 3 · 103 s in a wide dynamic range of 1−1010 electrons per orbit.Conclusions. The use of a CCD-based radiometer-comparator calibrated by responsivity on a synchrotron radiation source is particularly relevant in monitoring luminance contrast thresholds and spatial distribution of object and background brightness, as well as determining metrological characteristics of optoelectronic measuring instruments, including CCD cameras, radiometers, spectroradiometers and photometers.